Assessment of Tax Risks Arising from Personal Income Tax Agents - E. Е. Smirnova (Финансы: теория и практика, 2024)
Personal income tax (PIT) is one of the budget-forming taxes in the Russian Federation, therefore, an important direction of tax planning is the  assessment  of  risks  arising  from  both  tax  agents  (at  the  micro  level)  and  the state represented by tax authorities (at the macro level). The subject of the study is tax risks on personal income tax, and the purpose is to develop proposals for their assessment and reduction. Objectives: to classify tax risks according to  personal  income  tax;  to  clarify  the  quantitative  characteristics  of  tax  risks;  to  identify  directions of their decline. The relevance of the study is  dictated  by  the  need  to  study  theoretical  issues  and  practical aspects of the emergence of tax risks on personal income tax. The main methods of study are systemic, logical, theoretical cognition, scientific abstraction. The results  of  the  study include  the  following:  identification  of  the main types of tax risks for personal income tax and the development of a tax risks matrix for their assessment depending on residence, type of contract, amount of payment, court decisions, taking into account the possibility of identification, determination of amount of risk (arrears and penalties as well as  intention). Conclusions: in  the paper developed proposals for the assessment and reduction of tax risks under personal income tax: on the basis of the classification of tax risk (by subject, by basis of occurrence, by elements of taxation, by connection with tax checks, by types of risks, by the time of identification of tax risk, as well as taking into account the  regional specifics) the amount of possible tax risk is calculated on the example of specific income  (premium, financial assistance, gift) a tax risk matrix has been developed for practical application, which will enable to assess and rank tax schemes aimed at reducing tax obligations under personal income tax.